Inauguration of a new journal with focus on sustainable intensification of crop production: Crop and Environment - Peng, Shaobing; Xiong, Dongliang; You, Liangzhi (Elsevier, 2022)
We are pleased to announce the inauguration of Crop and Environment, an international peer-reviewed, open-access journal published by Elsevier in partnership with Huazhong Agricultural University, China. Crop and Environment aims to provide a forum for information exchange on innovation, research, and extension related to crop production science, environmental effects on crop production, and the impact of crop production on the environment.